Pulmonary arterial hypertension with abnormal V/Q single-photon emission computed tomography - Chan, K; Ioannidis, S; Coghlan, J; Hall, M; Schreiber, B (Elsevier, 2017)
Objectives: This study aims to evaluate the incidence and clinical outcomes of abnormal ventilation/perfusion (V/Q) SPECT without thromboembolism, especially in group I pulmonary arterial hypertension (PAH) patients. Background: AHA/ACC and ESC guidelines recommend V/Q scan for screening for chronic thromboembolic pulmonary hypertension (CTEPH). The significance of patients with abnormal V/Q SPECT but no thromboembolism demonstrated in further investigations remained unclear. A distinct pattern of global patchy changes not typical of thromboembolism is recognised but guidelines for reporting these in the context of pulmonary hypertension is lacking. Methods: A total of 136 patients underwent V/Q SPECT and right heart catheterization showing mean pulmonary arterial pressure (mPAP) ≥25mmHg were included. V/Q SPECT were reported using EANM criteria for pulmonary embolism followed by CT pulmonary angiography (CTPA) screening for positive thromboembolisms and further invasive pulmonary angiogram for distal thromboembolisms. The abnormal V/Q SPECT images were further analysed according to perfusion pattern into focal or global perfusion defects. Results: V/Q SPECT showed thromboembolic disease in 44 patients but 19 of these have no thromboembolisms demonstrated by pulmonary angiography. 15/19 (78.9%) of these patients had group I PAH and the majority had diffuse patchy perfusion defects. After re-defining V/Q SPECT images according to the perfusion pattern, those with global perfusion defects had higher mPAP compared to patients with focal perfusion defects and normal scans (mean difference +13.9mmHg and +6.2mmHg respectively, p=1.54x10-4 ) as well as higher pulmonary vascular resistance (mean difference +316.6 ARU and +226.3 ARU respectively, p=0.004). Among patients with PAH, global perfusion defects were associated with higher all-cause mortality with hazard ratio 5.63 (95% CI 1.11-28.5) compared to those with focal or no perfusion abnormalities. Conclusion: There is a high incidence of abnormal V/Q SPECT scans in non-thromboembolic PH. Further studies are needed to investigate the poor outcome associated with abnormal V/Q SPECT in the context of PAH.